2015
DOI: 10.1162/comj_a_00284
|View full text |Cite
|
Sign up to set email alerts
|

Sound Synthesis Procedures as Texts: An Ontological Politics in Electroacoustic and Computer Music

Abstract: This article describes a set of "textual" technological practices that have been emerging over the past decade in the work of underground electroacoustic and computer music composers, focusing particularly on Florian Hecker and Russell Haswell. Guided by methodological insights from the field of software studies, the article zooms in on two computer programs, PulsarGenerator and GENDYN, presenting a genealogical analysis of them as cultural objects and outlining how these lines of descent are aestheticized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Equalisation can come very close to extreme calculative rationalisation, when 'acoustic events' are divided into temporal micro-slices (or 'grains') which will then be recombined in changed ways through 'granular synthesis' (Roads, 2004: 86). It can also be achieved through stochastic processes, whereby sequences of music, or even a whole musical piece, are produced through an algorithm which synthesises sounds undergoing aleatory variations (as in Xenakis' GENDYN programme, a reference for contemporary computer music, including glitch, noise and 'extreme' computer music -see Haworth, 2015). Echoing Nicolas' argument of an increased dependency of contemporary music on mathematics, Paul Théberge has suggested that music has been transformed 'from an art of instrumental sound, performance and compositional technique to one of mathematics, digital technologies and algorithmic operations' (Théberge, 2015: 330).…”
Section: Sound and Flavour Combinatoricsmentioning
confidence: 99%
“…Equalisation can come very close to extreme calculative rationalisation, when 'acoustic events' are divided into temporal micro-slices (or 'grains') which will then be recombined in changed ways through 'granular synthesis' (Roads, 2004: 86). It can also be achieved through stochastic processes, whereby sequences of music, or even a whole musical piece, are produced through an algorithm which synthesises sounds undergoing aleatory variations (as in Xenakis' GENDYN programme, a reference for contemporary computer music, including glitch, noise and 'extreme' computer music -see Haworth, 2015). Echoing Nicolas' argument of an increased dependency of contemporary music on mathematics, Paul Théberge has suggested that music has been transformed 'from an art of instrumental sound, performance and compositional technique to one of mathematics, digital technologies and algorithmic operations' (Théberge, 2015: 330).…”
Section: Sound and Flavour Combinatoricsmentioning
confidence: 99%
“…6. Far from a straightforward valorization of "practice" (for critiques or extensions of the "practice turn" in music studies, see Born 2010; Steingo 2018), my approach continues the ongoing engagement with actor-network theory, ontology, and new materialism in ethnomusicology (Bates 2012;Risk 2013;Roda 2014Roda , 2015Steingo 2018), and music studies at large (Born 2005(Born , 2015Haworth 2015;Piekut 2013Piekut , 2014. Although I draw primarily on Barad (2007), related ideas about "mattering" animate Latour's (2004) and Stengers's (2010Stengers's ( , 2011 work on "cosmopolitics" and Mol's (1999) discussion of "ontological politics.…”
Section: Meeting the Garden Halfway: A Tangle Of Practices Ontologies Actorsmentioning
confidence: 99%
“…Speech processing has been widely applied in composition and songwriting, record production, and entertainment. Unlike simple speech synthesis, music melody synthesis has two additional processing steps: tone detection and transformation [5,6]. Wenner et al [7] preprocessed the musical melody synthesis corpus through automatic note segmentation and voiced/unvoiced sound recognition, constructed a high-quality music melody synthesis system, and proposed a music melody adjustment algorithm, which functions as an adaptive filter capable of detecting musical note cycles.…”
Section: Introductionmentioning
confidence: 99%